Subverting Feminine Identity: Reinvention of Sailor Moon‘s Girl Power in Violet Evergarden - Azzi, Amanda (Université d'Ottawa | University of Ottawa, 2021)
During the 1990s, Sailor Moon and the Girl Power movement came face to face with young girls worldwide As an anime based on the shōjo manga Sailor Moon, the adaptation set a precedent for heroic feminism within the male-dominant industry. In modern Japanese literature—namely light novels—we encounter other female heroines who reinvent the notion of Girl Power by challenging the weaponized femininity presented in Victoria Newsom and Joanette Quenby‘s work around the reclamation of the girlish and alternative gender identities. Moreover, as a new form of fiction, light novels challenge older forms of Japanese literature—mostly manga—which continue to subvert the dissemination of this Girl Power. Consequently, this article further develops the idea that the modern anime Violet Evergarden, based on a light novel of the same name, reinvents Sailor Moon‘s Girl Power through the modern form of Japanese literature and the titular protagonist‘s otherworldly presence within a liminal space Magical girl anime typically limits itself to the socially constructed masculine heroism that Violet reinvents through her newfound strength and subversion of the feminine.
Keywords: manga; girl power; anime; magical girl; shōjo; light novel